Mobile computing as a tool in orthopaedic surgery residency training: a pilot study. Issue 4 (July 2015) - Varcadipane, Joseph C.; Dupaix, John P.; Nishimura, Stephanie; Chun, Maria; Scarcella, Nicholas; Belcher, Gary; Castelo, Jamie; Atkinson, Robert E.
Abstract : Background: As mobile computing technology continues to improve and grow in popularity, such devices are becoming more prevalent in modern medical practice and education. The purpose of this study was to quantify resident perceptions, usage patterns, and the utility of an iPad/mobile tablet computer in orthopaedic surgery residency training. Methods: A total of nine residents were included in the pilot study. A mixed methods approach (i.e. quantitative and qualitative methods) was utilized, given the relatively small sample size. Each resident participated in a baseline survey and post survey for the study period of 1 academic year. The surveys attempted to quantify the usage patterns in three main areas: (1) resident education, (2) clinical practice, and (3) patient education. In addition, a qualitative component (i.e. focus group) was conducted to develop themes related to usage patterns. To determine quantitative effect, resident percentile score changes on in-training examination were compared before and after implementation of the pilot study with paired t-testing. A Student t-test was used to compare change in mean program percentile rank on in-training examination before and after implementation Results: An overall increase in usage of portable computing (the iPad) as a way for residents to study as well as perform administrative and clinical duties was observed. There was a trend towards increased overall study time and study time "on-the-go" as participants indicated increased study time in "hospital work areas." There were also observed increases in professional activities such as referencing treatment options and ordering lab tests. Conversely, few participants reported using the iPad for accessing radiographic studies or demonstrating conditions to patients. The focus group discussion emphasized improved efficiency gained by having quick and easy access to reference and study material. However, the lack of informational technology support and infrastructure for integration with the electronic medical records (EMRs) and Picture Archiving and Communication System (PACS) hindered clinical and patient educational usage. Mean annual increase in in-training examination scores increased from 3.4 to 8.1 percentile points, similarly the mean annual program percentile rank based on scores increased from the 72nd to the 85th percentile. Conclusions: Mobile computers such as the iPad can be useful for residents in orthopaedic surgery by improving their access to educational resources and allowing more study time "on-the-go" which may lead to more time studying in general and improvement in test scores. Patient education and clinical usage is possible but information technology support is needed for these devices to be used to their fullest potential.